2004
DOI: 10.1017/s0305000903005889
|View full text |Cite
|
Sign up to set email alerts
|

Learning by ear: on the acquisition of case and gender marking by German-speaking children with normal hearing and with cochlear implants

Abstract: The acquisition of case and gender marking on the definite and indefinite article was studied in a sample of 6 normally-hearing children and 9 children with cochlear implants. Longitudinal spontaneous speech data are used. Children were matched by MLU, with 4 MLU levels: 1·8, 2·8, 3·6, 4·8. Age ranges for normally-hearing children were 1;4 to 3;8 and for children with cochlear implants 1;8 to 7;0. Frequencies of correctly marked article forms increased over MLU but less so in the hearing-impaired group. In bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 14 publications
8
77
0
2
Order By: Relevance
“…These results closely resemble what other researchers have observed (Le Normand, 2004;Szagun, 2004). Both Szagun and Le Normand found that progress in lexical development was notably quicker than acquisition of grammar rules.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results closely resemble what other researchers have observed (Le Normand, 2004;Szagun, 2004). Both Szagun and Le Normand found that progress in lexical development was notably quicker than acquisition of grammar rules.…”
Section: Discussionsupporting
confidence: 91%
“…Several of Blanca's characteristics suggest that CS might have played an important role. As regards the use of protoarticles, Szagun (2004) had found that CI children (non-CS) used them for a longer period than NH children. Blanca, on the other hand, seemed to use few protoarticles.…”
Section: Discussionmentioning
confidence: 99%
“…In German, the acquisition of inflectional noun morphology is a particularly difficult task that takes longer than the acquisition of basic syntactic rules. While word order in sentences, that is, the verb-second placement in main clauses, is acquired around the age of 2.6 (Clahsen, 1999), full mastery of plural or case marking takes several years until school age (Kauschke, Kurth, & Domas, 2011;Laaha, Ravid, Korecky-Kröll, Ravid, & Dressler, 2006;Szagun, 2004). The acquisition of the German plural system has been investigated using spontaneous speech as well as elicitation data.…”
Section: The Interface Of Prosody and Morphology In Language Acquisitmentioning
confidence: 99%
“…More recently, investigations based on larger samples have been added (Kauschke & Hofmeister, 2002;Szagun, 2001aSzagun, , 2001b) and a single case study based on very extensive speech sampling (Behrens, 2001). These recent analyses have addressed vocabulary growth (Kauschke & Hofmeister, 2002), grammatical growth (Szagun, 2001a), and the acquisition of specific morphological paradigms, such as plural marking (Behrens, 2001;Szagun, 2001b) or case and gender marking (Szagun, 2004). However, normative data on vocabulary and grammatical growth in German-speaking children are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The age span of 1;6-2;6 is a very important period of development when children in different languages typically move from first words to grammar (Bates, Bretherton & Snyder, 1988;Berglund & Eriksson, 2000;Caselli et al, 1999;Fenson et al, 1994;Maital et al, 2000;Zink & Lejaegere, 2002). In German, children start acquiring inflectional markings in nearly all morphological paradigms during this period (Behrens, 1993(Behrens, , 2001Miller, 1976;Mills, 1985;Szagun, 2001aSzagun, , 2001bSzagun, , 2004. This includes noun plural marking, gender and case marking, present tense verb morphology, past participle, as well as auxiliary forms.…”
Section: Introductionmentioning
confidence: 99%